Ethiopian immigrants to Israel: The persistence and transformation of African values and practices in art and life. Issue 6 (2nd November 2019) - Greenfield, Patricia M.; Rotem, Oshrat Sulika; Weinstock, Michael
Abstract : We present a qualitative interdisciplinary study of seven Ethiopian potters who immigrated to Israel as adults. Data sources include cultural products (their clay sculptures), interviews, and archival photos at the time of immigration. Together these data sources show how these women carried African values (procreation, family closeness, sharing, and respect for elders) and memories of subsistence activities to Israel. They also show how the women expressed these values and practices in their sculptures. Additionally, findings reveal the contrasting, often conflicting, cultural values and practices that the women met in the broader Israeli society. Furthermore, we document spontaneous stylistic changes in the pottery in adaptation to the new environment. In Ethiopia, potters learned to work in clay by observing their mothers in an apprenticeship process. A new project will give Ethiopian immigrant potters an opportunity to use apprenticeship methods to transmit their techniques to a new generation of Israelis.